2018
DOI: 10.3390/admsci8010005
|View full text |Cite
|
Sign up to set email alerts
|

Frank and Fearless: Supporting Academic Career Progression for Women in an Australian Program

Abstract: The underrepresentation of women in senior positions continues to be a major challenge in higher education and most other industries. In Australia, the career trajectory for academic women stalls at a lower level than that of their male counterparts. Concern about this situation in one Australian university led to the design and delivery of a career progression program to support women's advancement from senior lecturer to associate professor. This study details the main features of the program, designed to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…Another interesting study from the context of higher education in Australia that takes a constructive tone is represented by the article titled "Frank and Fearless: Supporting Academic Career Progression for Women in an Australian Program" (Parker et al 2018). When a 2009 analysis of data at a large Australian university identified that gender parity at the level of lecturer and senior lecturer did not translate to gender parity at more senior levels, a targeted program (a "Career Progression for Women" course) was developed to support the advancement of more women from senior lecturer to associate professor rank.…”
mentioning
confidence: 99%
“…Another interesting study from the context of higher education in Australia that takes a constructive tone is represented by the article titled "Frank and Fearless: Supporting Academic Career Progression for Women in an Australian Program" (Parker et al 2018). When a 2009 analysis of data at a large Australian university identified that gender parity at the level of lecturer and senior lecturer did not translate to gender parity at more senior levels, a targeted program (a "Career Progression for Women" course) was developed to support the advancement of more women from senior lecturer to associate professor rank.…”
mentioning
confidence: 99%
“…However, a literature search found 16 WLPs that outlined a program framework. Of those 16, 11 offered some information about the topics used in the programs (see (Clarke, 2011;Ely et al, 2011;Parker et al, 2018;Pollitt, 2014;Van Oosten et al, 2017).…”
Section: Program Inclusions That Benefit Women Leadersmentioning
confidence: 99%
“…Where identified, data were gathered through post program interviews or surveys and, in one instance, on the basis of an autoethnographic research methodology (Selzer et al, 2017). Quantitative surveys were used in one program to assess the benefits of specific course components (Parker et al, 2018). Across the six programs the strongest impacts were enhanced leadership skills (Clarke, 2011;Harris & Leberman, 2012;Parker et al, 2018;Selzer et al, 2017;Van Oosten et al, 2017;White, 2012) and creation of new networks as support (Clarke, 2011;Harris & Leberman, 2012;Parker et al, 2018;Selzer et al, 2017;Van Oosten et al, 2017).…”
Section: Program Inclusions That Benefit Women Leadersmentioning
confidence: 99%
See 2 more Smart Citations